Using Herringbone Graphic Organizer Strategy to Enhance Students’ Reading Comprehension - Ihsan Umraity; Bustami Usman; Iskandar Abdul Samad (Universitas Syiah Kuala, 2019)
This research aims at investigating the use of Herringbone Graphic Organizer Strategy (HGO) to enhance students’ reading comprehension and their responses toward the application of HGO. The true experimental design was used in this research in which the population involved four classes at Private Senior High School of SukmaBangsaLhokseumawe, consisting of 86 first grade students, while two classes were selected by using cluster random sampling as samples, namely X/Volcano as an experimental class, consisting of 18 students and X/Hargowilis as a control class, consisting of 20 students. The experimental class was taught by using HGO, whereas the control class was taught by using conventional strategy. The instruments used for data collection were tests and questionnaires. The tests were given for both the experimental and control class but the questionnaire was only distributed for experimental class students. The data obtained from the tests were analyzed by using the SPSS (statistical package for the social science) version 23 and the questionnaire was analyzed by using Likert scale. The analyses results indicated that HGO is able to enhance students' reading comprehension proven by the significance value of the t-test on the identifying main idea (p = 0.003), specific detail (0,001), and inference aspect (0.001). Therefore, since the probability is Sig. 0.05, then H0 is rejected. In addition, the students responded positively (79.16%) to the application of HGO. It can be concluded that HGO could enhance reading comprehension and develop the positive responses of the students.